On-Road Measurements of Ultrafine Particles and Associated Air Pollutants in a Densely Populated Area of Seoul, Korea - Kim, Kyung Hwan; Woo, Daekwang; Lee, Seung-Bok; Bae, Gwi-Nam (TAIWAN ASSOC AEROSOL RES-TAAR, 2015)
Spatial distributions of ultrafine particles (UFPs; 6 < D-p < 560 nm) and related gaseous and particulate pollutants were estimated from on-road measurements undertaken on busy roadways of Seoul, Korea, using a mobile laboratory (ML). The objectives of the study were to determine the spatial variations in UFP size distributions and concentrations of associated gaseous and particulate pollutants and to observe the relationships of UFP number concentrations with other pollutants on roadways in an urban area in Korea. The pollutants associated with diesel vehicles such as black carbon (BC) and particle-bound polycyclic aromatic hydrocarbons (PM-PAHs) exhibited a high determination coefficient (r(2) = 0.65), indicating the influence of diesel vehicles on emissions in the study area. Further supporting evidence for the influence of diesel vehicles on emissions was given by the higher determination coefficients of PM-PAHs and BC concentrations with larger size-classified particles, ranging from 60 < D-p < 220 nm, than with total UFP number concentrations or smaller particles in the 6 < D-p < 60 nm size range. Peak concentrations of measured pollutants were observed mostly at intersections, reflecting the relationships of transient driving modes (i.e., deceleration and acceleration) with emissions of UFPs, associated pollutants, and concentrated traffic volumes at such locations.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; REAL-TIME CHARACTERIZATION; MOTOR-VEHICLE EMISSIONS; SIZE DISTRIBUTIONS; COMBUSTION AEROSOLS; MODE PARTICLES; MAJOR HIGHWAY; MEXICO-CITY; URBAN; SUBMICROMETER